Coaching primary care clinics for HPV vaccination quality improvement: Comparing in-person and webinar implementation. Issue 1 (20th February 2018) - Calo, William A; Gilkey, Melissa B; Leeman, Jennifer; Heisler-MacKinnon, Jennifer; Averette, Chrystal; Sanchez, Stephanie; Kornides, Melanie L; Brewer, Noel T
Abstract : Providers who received quality improvement coaching reported more positive attitudes and self-efficacy toward HPV vaccination. In-person coaching reached more providers per clinic than webinar coaching. Abstract: State health departments commonly use quality improvement coaching as an implementation strategy for improving low human papillomavirus (HPV) vaccination coverage, but such coaching can be resource intensive. To explore opportunities for improving efficiency, we compared in-person and webinar delivery of coaching sessions on implementation outcomes, including reach, acceptability, and delivery cost. In 2015, we randomly assigned 148 high-volume primary care clinics in Illinois, Michigan, and Washington State to receive either in-person or webinar coaching. Coaching sessions lasted about 1 hr and used our Immunization Report Card to facilitate assessment and feedback. Clinics served over 213, 000 patients ages 11–17. We used provider surveys and delivery cost assessment to collect implementation data. This report is focused exclusively on the implementation aspects of the intervention. More providers attended in-person than webinar coaching sessions (mean 9 vs. 5 providers per clinic, respectively, p = .004). More providers shared the Immunization Report Card at clinic staff meetings in the in-person than webinar arm (49% vs. 20%; p = .029). In both arms, providers' belief that their clinics' HPV vaccination coverage was too low increased, as did their self-efficacy to help their clinics improve ( p < .05). Providers rated coaching sessions in the two arms equally highly on acceptability. Delivery cost per clinic was $733 for in-person coaching versus $461 for webinar coaching. In-person and webinar coaching were well received and yielded improvements in provider beliefs and self-efficacy regarding HPV vaccine quality improvement. In summary, in-person coaching cost more than webinar coaching per clinic reached, but reached more providers. Further implementation research is needed to understand how and for whom webinar coaching may be appropriate.